Hormonal changes in papaya seedlings subjected to progressive water stress and re-watering - Mahouachi, J.; Arbona, V.; Gómez-Cadenas, A.
Changes on abscisic acid (ABA), jasmonic acid (JA)and indole-3-acetic acid (IAA)levels were investigated in papaya seedlings (Carica papaya L.)cv. ''Baixinho de Santa Amalia'' under progressive water stress and subsequent rehydration. Also, the behaviour of leaf gas exchange and leaf growth was determined under stress condition. The results indicated that ABA and JA differ in their pattern of change under water stress. ABA continuously increased in leaves and roots during the whole period of stress whereas JA showed a sharp increase and a later decrease in both organs. Re-watering reduced rapidly (24 h)leaf and root ABA to control levels whereas the influence on JA levels could not be assessed. Drought and recovery did not alter IAA levels in leaf and root tissues of papaya seedlings. In addition, water stress reduced stomatal conductance, photosynthetic rate, transpiration rate, the percentage of attached leaves and leaf growth. Rehydration reverted in few days the effects of stress on leaf growth and gas exchange parameters. Overall, the data suggest that ABA could be involved in the induction of several progressive responses such as the induction of stomatal closure and leaf abscission to reduce papaya water loss. In addition, the pattern of accumulation of JA is compatible with a triggering signal upstream ABA. The unaltered levels of IAA could suggest a certain adaptive ability of papaya to maintain active physiological processes under progressive drought stress.
Keywords: ABSCISIC ACID; ABSCISSION; INDOLE-3-ACETIC ACID; JASMONIC ACID; LEAF GAS EXCHANGE; SOIL MOISTURE